Perancangan Sistem Mobile Bulletin untuk Implementasi Smart Poster NFC dengan Tokenisasi Salt - Audy; Marcel Bonar Kristanda; Seng Hansun (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Bulletin board is a medium for sharing information in Multimedia Nusantara University. However, feasibility study showed that bulletin board is not effective to be used as a medium for information dissemination in UMN. Apart from the user side, the development of UMN campus building also become an obstacle in using traditional bulletin board. NFC technology is a type of short-range wireless technology, which widely been used in developed countries in everyday life. One concrete manifestation of NFC technology implementation is Smart Poster. Therefore, based on feasibility study that had been done, the design of Mobile Bulletin system for implementing Smart Poster with NFC technology and Salt Tokenization method is made. This paper has succeeded to make the design of the overall system architecture and user interaction overview. The proposed architecture design shows that this system can solve conventional bulletin board problem, both for students and administrators.